The Policy Gap on Food Loss and Waste Reduction in Indonesia - Sidik Pramono; Sarah Anggraeni Suhartono (Jurnal Ilmu Manajemen Terapan, 2026)
Indonesia faces an increasingly serious environmental crisis due to high levels of food loss and waste (FLW), which significantly contribute to waste generation, greenhouse gas emissions, and economic inefficiency. Despite global commitments to sustainable development through the Sustainable Development Goals (SDGs), policy responses in Indonesia remain fragmented. This study aims to examine the policy gap in FLW reduction through an analysis of the regulatory framework, institutional arrangements, and implementation challenges. The study employed a qualitative approach with a descriptive-normative design through a literature review of policy documents, regulations, and reports. The results revealed key gaps in regulatory fragmentation, weak cross-sectoral policy integration, and institutional coordination challenges. Existing policies tend to position FLW as a downstream issue in waste management, not yet part of the overall food system. This study concludes that without a comprehensive and integrated policy framework and strong institutional leadership, FLW reduction efforts in Indonesia will not be optimal. Strengthening policy coherence, governance coordination, and a holistic food system approach are key to supporting sustainable development, food security, and reducing environmental pressures in Indonesia.